2014
DOI: 10.1002/we.1726
|View full text |Cite
|
Sign up to set email alerts
|

A study on rotational augmentation using CFD analysis of flow in the inboard region of the MEXICO rotor blades

Abstract: This work presents an analysis of data from existing as well as new full-rotor computational fluid dynamics computations on the MEXICO rotor, with focus on the flow around the inboard parts of the blades. The boundary layer separation characteristics on the airfoil sections in the inboard parts of the rotor are analysed using the pressure and the skin friction data at a range of angles of attack. These data are used to gain insight on the relative behaviour of separated boundary layers in 3D flow compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…This effect delays the stall onset and enhances the lift force as compared to non-rotating blades operating at the same AoA. The Himmelskamp effect, also known as stall delay or rotational augmentation, has been studied by many authors both experimentally (Schreck and Robinson, 2002;Sicot et al, 2008;Ronsten, 1992) and numerically (Guntur and Sørensen, 2014;Herráez et al, 2014;Schreck et al, 2007), although it still remains far from being well understood and characterized. It mainly affects the blade root region and is known to be closely related to the existence of spanwise flows in the boundary layer.…”
Section: Spanwise Flows and Himmelskamp Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect delays the stall onset and enhances the lift force as compared to non-rotating blades operating at the same AoA. The Himmelskamp effect, also known as stall delay or rotational augmentation, has been studied by many authors both experimentally (Schreck and Robinson, 2002;Sicot et al, 2008;Ronsten, 1992) and numerically (Guntur and Sørensen, 2014;Herráez et al, 2014;Schreck et al, 2007), although it still remains far from being well understood and characterized. It mainly affects the blade root region and is known to be closely related to the existence of spanwise flows in the boundary layer.…”
Section: Spanwise Flows and Himmelskamp Effectmentioning
confidence: 99%
“…Centrifugal force: the centrifugal force that acts on the bottom of the boundary layer (i.e. the region where the flow is not detached from the surface) pushes the flow towards the tip (Du and Selig, 1999;Lindenburg, 2003;Guntur and Sørensen, 2014).…”
Section: The Source Of the Spanwise Flowsmentioning
confidence: 99%
“…Therefore, we assume that comparing 2D and 3D characteristics is an acceptable method for assessing the role of the rotational effects. This is also the most common way to do it [10,14,16,18,20,29,30,34,38].…”
Section: The Mexico Experimentsmentioning
confidence: 99%
“…In a later work, Schreck et al studied the same turbine using RANS with the kω − SST turbulence model and ascribed the rotational effects to stationary vortical structures located on the upper blade surface [19]. Very recently, Guntur and Sørensen [20] studied the MEXICO turbine with RANS and the kω model, observing that on rotating blades there is a postponement of the separation point. Furthermore, it was concluded that the AoA at which separation is initiated is higher in 3D compared with 2D.…”
Section: Introductionmentioning
confidence: 99%
“…This is to be expected although the reason is under discussion (Herráez et al, 2016) at the blade root area and has been attributed to span-wise pressure gradients (Schreck et al, 2010) and centrifugal forces on the boundary layer (Guntur and Sørensen, 2014). SFA values increase as λ decreases.…”
mentioning
confidence: 85%